1989
DOI: 10.1111/j.1432-1033.1989.tb14885.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid partial degradation of DDT by a cytochrome P‐450 model system

Abstract: Heme compounds, in combination with a reducing agent and oxygen, can express various activities of cytochrome P-450 enzymes. In the present study it was found that a mixture of hemin and excess cysteine was able to degrade the insecticide DDT partially. The major products were three water-soluble, non-toxic conjugates of DDT metabolites with cysteine which had lost two or three of the five chlorine atoms of DDT per molecule and whose structures were elucidated by gas chromatography/mass spectrometry. In 0.05 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Strong inverse associations were observed between cysteine and pp′DDT, pp′DDE, pp′DDD, and op′DDT. Consistent with the present findings, Langen et al [16] showed in vitro that a mixture of hemin and excess cysteine was able to partially degrade DDT. Although the concentration of cysteine in tissues is much lower than the concentration used in this in vitro system, this finding suggests that cysteine, along with other amino acids, could influence the metabolism and excretion of DDT in vivo .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Strong inverse associations were observed between cysteine and pp′DDT, pp′DDE, pp′DDD, and op′DDT. Consistent with the present findings, Langen et al [16] showed in vitro that a mixture of hemin and excess cysteine was able to partially degrade DDT. Although the concentration of cysteine in tissues is much lower than the concentration used in this in vitro system, this finding suggests that cysteine, along with other amino acids, could influence the metabolism and excretion of DDT in vivo .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, indole-3-carbinol, a component of cruciferous vegetables, alters DDT metabolism and reduces its estrogenic effects by favoring metabolism through the 2-hydroxyoestone pathway, a more benign pathway with regard to breast cancer risk compared to the 16-alpha-hydroxyoestrone pathway [15]. Langen et al [16] showed that a mixture of hemin and excess cysteine was able to degrade DDT partially, where the degradation reaction catalyzed by the hemin-cysteine model was 8 × 10 4 times faster than the uncatalyzed reaction and produced 3 water-soluble, nontoxic, cysteine-containing conjugates. Other animal studies suggest that nutrient levels may be influenced by xenobiotics.…”
Section: Introductionmentioning
confidence: 99%
“…In other organisms cytochrome P450 enzymes anchored on the endoplasmic reticulum participate in the detoxification of xenobiotics, drug, and pesticide metabolism (Lah et al, 2011;Langen et al, 1989;Werck-Reichhart and Feyereisen, 2000). Results of computational analyses combined with subcellular localization of CYP5013C2-GFP suggested that CYP5013C2 was a typical endoplasmic reticulum-anchored protein like CYP3A4 in Saccharomyces cerevisiae (Liao et al, 2006) .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, of all the mixtures of natural proteins with hemin and cysteine tested for their ability to degrade DDT only a mixture containing ß-casein had an activity comparable to that of DBP, hemin and cysteine [23] the main reason for this probably being the relatively strong binding of both DDT and hemin by ß-casein (K D , 5.5x10 -5 M and 5x10 -5 M, respectively). Because of its broad spectrum of biological functions (nutrient, casomorphin activity [29], DDT binding etc.)…”
Section: B Myoglobin F-helix -Dbp Fusion Proteinmentioning
confidence: 93%
“…4a) whose affinity for the insecticide (K D , 9x10 -7 M in buffer/ethanol, 1:1) was >1000 times higher than that of serum albumin, a well-known carrier of apolar metabolic intermediates and xenobiotics in the circulation. Together with hemin and excess cysteine, this peptide accelerated DDT degradation reactions by a factor of approximately 3.5x10 5 as compared to the rate of uncatalyzed degradation [23]. In the mixture of DDT with DBP, hemin and cysteine, DBP improved the solubility of DDT for the degradation reactions catalyzed by the hemincysteine cytochrome P-450 model system [24].…”
Section: A β-Galactosidase -Artificial Ddt-binding Peptide (Dbp) Fumentioning
confidence: 98%